Beneficial Role of Imeglimin as Add-on Drug with other Oral Hypoglycaemic Agents for Patients with Type 2 Diabetes: A Single centre Prospective Interventional Study - Naima Parveen; Sachin Chittawar (Journal of Clinical and Diagnostic Research)
Introduction: With Type 2 Diabetes Mellitus (T2DM) affecting over 74 million individuals in India alone, achieving glycaemic control remains a persistent challenge, especially in patients inadequately managed with Oral Hypoglycaemic Agents (OHAs). The present study explored the potential of imeglimin, a novel antidiabetic drug targeting mitochondrial function, to bridge this gap. By addressing insulin resistance and β-cell dysfunction, imeglimin emerges as a dual-action therapy tailored for patients who are hesitant to initiate insulin. Aim: To assess the short-term effectiveness and safety of imeglimin in T2DM patients who are inadequately controlled on two or three OHAs and who are hesitant to initiate insulin therapy. Materials and Methods: The present prospective, single-arm, single-centre interventional study was conducted in the Department of Endocrinology, Harmony Dr. Sachin’s 360 Degree Diabetes Care Centre, Bhopal, Madhya Pradesh, India, from January 2023 to June 2023. A total of 75 patients meeting the inclusion criteria were enrolled. Baseline and 12-week post-treatment data were systematically recorded, including demographic variables, anthropometric measurements {height, weight, and Body Mass Index (BMI)}, and glycaemic parameters {Fasting Plasma Glucose (FPG), Postprandial Glucose (PPG), and Glycated Haemoglobin (HbA1c)}. Statistical analysis was conducted using one-way ANOVA to evaluate treatment effects. Results: The study population comprised 75 participants with a mean±Standard Deviation (SD) age of 57±10 years and a duration of diabetes diagnosis ranging from six months to 25 years. Males represented a predominant 54.6% of the study cohort. Following 12 weeks of imeglimin treatment, HbA1c levels demonstrated a mean reduction of 1.1% (p-value=0.004) compared to baseline values. Furthermore, FPG levels decreased by a mean of 49.3 mg/dL (p-value=0.013), while PPG exhibited a mean reduction of 79.4 mg/dL (p-value=0.020). The most frequently reported treatment-emergent adverse events were gastrointestinal in nature. Conclusion: Imeglimin demonstrated short-term effectiveness in enhancing glycaemic control as an adjunct therapy to existing OHAs in T2DM patients who are hesitant to initiate insulin. The treatment was well tolerated, with gastrointestinal issues being the primary adverse effect. Further extensive studies with larger sample sizes are warranted to validate these findings and ascertain the long-term effects of imeglimin in T2DM management.